KETERLIBATAN ORANGTUA DALAM MENCEGAH ANGKA PUTUS SEKOLAH PADA MASYARAKAT MISKIN DI KELURAHAN TANJUNG MAS SEMARANG - Annisa Fitria Rahma Hastutik; Decky Avrilianda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
If the problem of dropping out of school is not anticipated early on, the dropout rate will increase significantly. Parents with low socioeconomic status often struggle to meet basic household needs, especially the cost of their children's education. This study aims to analyze various types of parental involvement in the education of children from poor families in Tanjung Mas Village, Semarang. The method used is descriptive qualitative with data triangulation techniques such as observation, documentation, and interviews. The research findings indicate that parental involvement impacts parenting, communication, volunteering, learning at home, decision-making, and community collaboration. Parental involvement can increase a child's desire to learn and reduce the risk of dropping out of school. However, economic factors are the main factor, along with parents' low awareness. According to this research, parental involvement is one of the factors that play a role in reducing dropout rates in poor urban communities.